An Evaluation of Fetal Heart Rate Characteristics Associated With Neonatal Encephalopathy: A Case-Control Study. Issue 3 (September 2019) - Frey, H.A.; Liu, X.; Lynch, C.D.; Musindi, W.; Samuels, P.; Rood, K.M.; Thung, S.F.; Bakk, J.M.; Cheng, W.; Landon, M.B.
Abstract : ( BJOG . 2018;125(11):1480–1487) Neonatal encephalopathy (NE) is characterized by abnormal neurological function that presents with decreased level of consciousness or seizures, difficulty maintaining respirations, and abnormal reflexes or tone. This clinical condition is identified shortly after birth with an incidence of 2 to 6/1000 live births. There is incomplete understanding of the etiology of NE and no evidence-based interventions to prevent its occurrence. The objective of the study was to identify predelivery fetal heart rate (FHR) characteristics associated with NE. The hypothesis was category III FHR tracings would be associated with NE.